2018
DOI: 10.1080/0167482x.2017.1415881
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal smoking and postpartum depression: a meta-analysis

Abstract: Our meta-analysis indicated that prenatal smoking was associated with postpartum depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 35 publications
0
21
1
4
Order By: Relevance
“…Those exposed to second-hand smoking were at non-significantly higher risk of subsequent depressive symptoms (OR=1.51, 95% CI: 0.93-2.09). Additionally, four prospective studies of 3,736 pregnant women found that prenatal smoking was associated with an almost three-fold increased risk of postpartum depression (OR=2.88, 95% CI: 0.99-8.39), although with high heterogeneity (I 2 =89.3%) and effects breaching the threshold for statistical significance (p=0.052) 45 (see Table 3).…”
Section: Smoking and Risk Of Common Mental Disordersmentioning
confidence: 99%
“…Those exposed to second-hand smoking were at non-significantly higher risk of subsequent depressive symptoms (OR=1.51, 95% CI: 0.93-2.09). Additionally, four prospective studies of 3,736 pregnant women found that prenatal smoking was associated with an almost three-fold increased risk of postpartum depression (OR=2.88, 95% CI: 0.99-8.39), although with high heterogeneity (I 2 =89.3%) and effects breaching the threshold for statistical significance (p=0.052) 45 (see Table 3).…”
Section: Smoking and Risk Of Common Mental Disordersmentioning
confidence: 99%
“…It could increase the risk for multiple adverse outcomes among themself, their partners, infants and families such as lead to selfnegative attitudes, self-harm and even suicidal intention, cause anxiety or depression of partner and even influence the behavioral, cognitive, physical health and social emotional development of their infants and children [1,[6][7][8]. Until now, the etiology of PPD remains unclear, although several risk factors have been identified [2,9], such as history of depression, lack of social support, cesarean delivery and prenatal smoking and so on [10][11][12][13][14]. With the attention of women's mental health, the influence of violence on mental health has attracted the closely attention of researcher.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings from the included studies, prenatal/perinatal exposure to active/passive smoke was largely found to increase the risk of developing postpartum depression and depressive symptoms in the postpartum period. Prenatal active smoking was found to be associated with an increased risk for postpartum depression, particularly those who smoked prior to pregnancy and continued to smoke during pregnancy into the postpartum period, compared to those women who quit during pregnancy and those who were non-smokers (Chen et al, 2018;Dagher & Shenassa, 2012;Frandsen, Thow, & Ferguson, 2017;Munafò, Heron, & Araya, 2008;Salimi et al, 2015;Vivilaki et al, 2016). The study by Underwood et al (2017) did not find an association between prenatal active smoking and postpartum depression.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…The main findings of this systematic review suggest that those exposed to active/passive smoke (cigarette/tobacco) during the prenatal/perinatal period had the greatest risk of developing postpartum depression and depressive symptoms in the postpartum period, compared to the other categories of toxicants. The literature does support a link between certain environmental toxicants and postpartum depression (Chen et al, 2018;Dagher & Shenassa, 2012;Frandsen et al, 2017;Munafò et al, 2008;Salimi et al, 2015;Sheffield et al, 2018;Singata-Madiliki et al, 2016;Vivilaki et al, 2016), although there were studies with inconclusive results and/or that found no association. These observations will be further explained throughout the following sections and the results for each category of toxicant will be interpreted.…”
Section: Main Findingsmentioning
confidence: 99%